2018
DOI: 10.1016/j.wroa.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced biofilm solubilization by urea in reverse osmosis membrane systems

Abstract: Chemical cleaning is routinely performed in reverse osmosis (RO) plants for the regeneration of RO membranes that suffer from biofouling problems. The potential of urea as a chaotropic agent to enhance the solubilization of biofilm proteins has been reported briefly in the literature. In this paper the efficiency of urea cleaning for RO membrane systems has been compared to conventionally applied acid/alkali treatment. Preliminary assessment confirmed that urea did not damage the RO polyamide membranes and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…Confirming the previous lab-scale studies [23], the results of this pilot-scale study show that urea cleaning and the standard acid/alkali cleaning are equally effective with regards to restoring the normalized feed channel pressure drop. Both cleaning strategies fulfilled the aim of chemical cleaning i.e., to restore the feed channel pressure drop of the membrane element when it exceeds 10–15% of the start-up value.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Confirming the previous lab-scale studies [23], the results of this pilot-scale study show that urea cleaning and the standard acid/alkali cleaning are equally effective with regards to restoring the normalized feed channel pressure drop. Both cleaning strategies fulfilled the aim of chemical cleaning i.e., to restore the feed channel pressure drop of the membrane element when it exceeds 10–15% of the start-up value.…”
Section: Discussionsupporting
confidence: 88%
“…Cleaning of the membrane modules at the DECO plant with chemicals such as NaOH and urea is therefore a suitable cleaning strategy, since the reaction mechanism of both the cleaning agents results in the removal of organic fouling [19,38]. Preliminary laboratory studies confirmed the compatibility of urea with the polyamide membranes [23], where urea was not found to damage the polyamide layer of the membrane.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Discussion P-limitation restricts microorganism growth but not biofilm formation in cooling tower systems A goal of this study was to investigate the efficiency of phosphate limitation as a preventive method for biofouling control in CTs. The applied short-term approach, based on nutrient dosages in the feed water, has been shown to be suitable for prediction of long-term biofouling (Sanawar et al 2017) and has been used to study membrane filtration systems (Siddiqui et al 2017;Sanawar et al 2018). The pilotscale experiment showed that: (1) active biomass growth in the CT was strongly inhibited under P-limited conditions compared with conditions with additional phosphate supplied (Figures 3 and 4); (2) the overall accumulation of organic matter was similar when all nutrients were supplied or under P-limited conditions with only organic carbon supplied ( Figure 3); (3) P-limitation caused a shift in bacterial community structure ( Figure 6) and seemed to promote the production of carbohydrates over proteins by the microorganisms in the extracellular matrix and to result in a more homogeneous biofilm (Supporting Information Figures S1 and S3).…”
Section: Deterioration In Water Quality Along the Feed Water Linementioning
confidence: 99%